Influence of time of onset of oestrus on embryo recovery in superovulated crossbred cows - KATHIRESAN, D; PALANISAMY, A; SELVARAJU, M; NACHIMUTHU, K (The Indian Journal of Animal Reproduction, 2023)
Superovulations were done with 2000 I.U.PMSG in 10 Sindhi Jersey cross bred cows on day 1 0 or 11 of the oestrous cycle and 25 mg of PGF2 d was injected for oestrus synchronization 48 hours after the superovulatory treatment. A.I. with double dose of forzen semen was carried out at 60, 72 and 84 hours after the PG injection. Embryo were collected by adapting non-surgical procedure. The donor cows exhibited oestrus at 48 hours of PGF2 injection produced more number of total and transferrable than cows exhibited oestrus before or after 48 hours of PG injection. It is concluded that time of onset of oestrus after PG injection has got influence on embryo recovery and quality of embryos in cross-bred cows.